THE COMPARATIVE ANALYSIS OF FUZZY LOGIC CONTROLLER CAN BE USED FOR CONTROLLING COMPLEX SYSTEMS - Kazak, V. N.; Shevchuk, D. O.; Vovk, V. G. (Problems of Informatization and Management, 2021)
In the article possibility of application of the fuzzy logic is considered. The computational mechanism and block-schematic of fuzzy logic controller is represented. The main principles are considered and the features of management on basis of the theory of fuzzy sets are revealed. Methods can be used for designing fuzzy logic controllers is considered.